Correlates of Portuguese college students' shyness and sociability - Félix Neto (1996)
This study investigated the relationship between shyness and sociability among 194 Portuguese college students. A factor analysis of the intercorrelation matrix of shyness and sociability items gave two distinct factors indicating that shyness and sociability are distinct personality dispositions. Shyness scores showed only a moderate negative correlation with sociability. Further, the measures of shyness and sociability had different patterns of correlations with other personality stales. The Portuguese translation of shyness and sociability scales seems sufficiently reliable and valid to warrant further use with Portuguese individuals.